Accuracy of Outcome Ascertainment in Long-Term Mortality After Coronary Artery Bypass Grafting - Kensuke Yokoi, MD; Atsushi Tanaka, MD; Goro Yoshioka, MD; Masahiko Hara, MD; Keiji Kamohara, MD; Koichi Node, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes)
Long-term outcome ascertainment can be affected by the follow-up performance and needs to use a different data source for more comprehensive data capture. However, a universal tracking system is absent in Japan, and long-term outcomes are often ascertained through electronic medical records (EMRs), the reliability of which is uncertain. In this study, we compared EMR-based and direct outreach–based collections on outcome ascertainment accuracy in 500 patients who underwent coronary artery bypass grafting. Mortality data for all patients were extracted from the EMR, as standard data collection. When patient death was not confirmed in the EMR, we enhanced to collect updated mortality information by direct outreach to patients, their family, or their physicians, as enhanced direct outreach data. As a result, the Kaplan-Meier curves found a notable separation between different data sources analyzed. Interestingly, mortality events in the latter half of the follow-up period (median, 6.5 years) were overestimated in the EMR-based data collection analysis because of the reduced number of actively tracked cases, highlighting a potential bias in the EMR-based data collection on long-term prognoses. Our findings suggest that an active follow-up strategy with better adherence will enhance the accuracy of long-term outcome ascertainment and be helpful to build more reliable real-world evidence.